INTEGRASI PENDIDIKAN KARAKTER TOLERANSI DALAM PEMBELAJARAN IPS PADA MATERI KEBERAGAMAN SOSIAL BUDAYA DENGAN PENDEKATAN KONTEKSTUAL DI KELAS 4 SDN 05 PADANG LAWEH - Puji Trisnawati; Putri Giofani; Putri Latifa; Lattifa Septia Nisda; Susi Ratna Sari (STKIP Subang, 2026)
This research is motivated by the importance of instilling tolerance character education in elementary school students in facing socio-cultural diversity in the community. The purpose of this study is to describe the integration of tolerance character education in social studies learning on socio-cultural diversity material with a contextual approach in grade IV of SDN 05 Padang Laweh. This study uses a qualitative approach with a descriptive research type. The subjects of this study consisted of grade IV students of SDN 05 Padang Laweh. Data collection techniques were carried out through questionnaires. Data analysis techniques were carried out by data reduction, data presentation, and drawing conclusions. The results of the study indicate that the integration of tolerance character education in social studies learning is carried out through learning activities that link the material to the real lives of students, such as respecting differences in ethnicity, culture, and friends' opinions. The contextual approach helps students understand the importance of tolerance through group discussions, cooperation, and active and meaningful learning activities. The values ​​of tolerance that emerge in learning include mutual respect, respect for differences, cooperation, and living in harmony in diversity. Thus, the contextual approach can support the strengthening of tolerance character education in social studies learning in elementary schools.